2015
DOI: 10.1021/la504382q
|View full text |Cite
|
Sign up to set email alerts
|

Operando X-ray Scattering and Spectroscopic Analysis of Germanium Nanowire Anodes in Lithium Ion Batteries

Abstract: X-ray diffraction (XRD) and Fourier transform extended X-ray absorption fine structure (EXAFS) analysis of X-ray absorption spectroscopy (XAS) measurements have been employed to determine structural and bonding changes, as a function of the lithium content/state of charge, of germanium nanowires used as the active anode material within lithium ion batteries (LIBs). Our data, collected throughout the course of battery cycling (operando), indicate that lithium incorporation within the nanostructured germanium oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
3
27
0
1
Order By: Relevance
“…This is similar to the lithiation process of the Ge reference electrode, which tends to form Li–Ge alloys and results in a significant decrease in peak magnitude. [ 19–21 ] The peak decrease is due either to the breakdown of the crystalline size or loss of crystallinity. This result clearly confirms that the reduction of LAGP is more pronounced at 80 °C than 25 °C, which is consistent with the results of HEXRD.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to the lithiation process of the Ge reference electrode, which tends to form Li–Ge alloys and results in a significant decrease in peak magnitude. [ 19–21 ] The peak decrease is due either to the breakdown of the crystalline size or loss of crystallinity. This result clearly confirms that the reduction of LAGP is more pronounced at 80 °C than 25 °C, which is consistent with the results of HEXRD.…”
Section: Resultsmentioning
confidence: 99%
“…Mohammad et al reported using a new oligosilylgermane compounds with weak GeH bonds as precursors for the rapid synthesis of Ge NWs in high yields (>80%), via an SLS mechanism, using In NPs as a seeding agent at a temperature range between 180 and 380 °C. Ge NWs also were synthesized using SFLS method, utilizing gold NPs as seeds . Sn seeded Ge NWs were grown onto stainless steel current collectors through a low cost SVG system .…”
Section: Preparation Of Ge Anodesmentioning
confidence: 99%
“…Silberstein et al studied the phase transformations within Ge NWs throughout the course of LIBs cycling using operando X‐ray techniques. Experiment data indicated that Li incorporation within the nanostructured Ge occurs heterogeneously, preferentially into amorphous regions over crystalline domains.…”
Section: Enhanced Electrochemical Performances Of Ge For Libsmentioning
confidence: 99%
“…The conversion between crystalline and amorphous Ge was believed to occur by virtue of amorphous Li 9 Ge 4 [49] or Li 15 Ge 4 [53] during Li-cycling. Very recently, amorphous Li-Ge was solidly confirmed with in-situ 7 Li NMR observation [54] and Operando X-ray techniques [55]. Herein, XRD measurements were carried out to identify the phase compositions of CoGCs/C-4 electrode after the 1 st discharge to 0.01 V (Figure 6b [16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%